Perancangan Sistem Otomatis Pemberi Pakan Ikan Berdasarkan Usia Berbasis IoT - Ios Jakub Sitompul; Habib Satria; Moranain Mungkin (Jurnal Ilmiah Teknik Informatika & Elektro (JITEK), 2023)
Cultivating catfish uses an artificial pond which is in great demand among the community. Most of the people who have jobs other than breeders choose this job to increase their income. Today's technological developments and advancements have a significant impact on how human society conducts every action. The authors created a program and were interested in using the term